Arctic angels - Smith, A. De Herries (Augustus De Herries), 1881-1945; Rowe, Clarence, 1878-1930 (Salt Lake City, UT : Project Gutenberg, 2024)
"Arctic Angels" by A. DeHerries Smith is a short story that falls under the category of adventure fiction, likely penned in the late 1920s. The narrative is set in the Arctic Northwest, showcasing the challenges faced by the Northwest Mounted Police in a harsh and unforgiving environment. The story revolves around themes of duty, survival, and the interaction between the police, local traders, and the indigenous Eskimo population. The plot centers on Sergeant Richard Cleaver, stationed at a remote detachment, who grapples with the moral dilemma of how to provide sustenance for starving Eskimos while dealing with the unscrupulous trader, Scarth. Tensions rise as Cleaver learns that Scarth has failed to feed his own starving huskies, and the desperation of the situation pushes him to hunt walrus for meat. The sergeant's determination to fulfill his promise to the indigenous people leads to a confrontation with the trader and a series of comical yet dire circumstances that test his leadership and integrity. Ultimately, the story resolves with a sense of triumph as Cleaver ensures that both the Eskimos and the dogs will receive the nourishment they desperately need, highlighting themes of compassion amidst adversity. (This is an automatically generated summary.)
Release date is 2024-04-25
Roger Frank and Sue Clark
Keywords: Short stories; Arctic regions -- Fiction; Royal North West Mounted Police (Canada) -- Fiction; Northwest Territories -- Fiction